A rapid strengthening approach for existing A-type RC frames in substations considering low disturbance: a finite-element-driven design study - Che, Wei-xian; Zhu, Wen-wei; Wang, Yan-feng; Guo, Jin-gen; Gao, Xin; Li, Lei; Niu, Gong-ke; Wang, Jing-he; Wang, Song (Frontiers in Materials, 2025)
The power system is an important lifeline engineering system, and substations play a crucial role in transferring the power supply. To ensure the reliability of the power supply, the safety of the existing A-type reinforced concrete frame cannot be ignored. To avoid long-term power outages and high overall costs, this study considered and analyzed the use of a low-interference rapid reinforcement method. All components used in this method are produced in the factory, and no grouting or welding operations are required on site. Additionally, ABAQUS numerical simulation was used to study the mechanical properties of the strengthened A-type reinforced concrete frame and analyze the effectiveness of the proposed reinforcement method. The results show that strengthening the A-type reinforced concrete frame by this method has increased its ultimate bearing capacity, initial stiffness, and energy dissipation capacity by 184%, 28%, and 52%, respectively. The proposed method improves the overall performance. This study provides a reference for reinforcing similar reinforced concrete structures in substations.